Interaction between cattle organism and some factors of environment - V I Rodin (RUDN Journal of Agronomy and Animal Industries, 2012)
Concerning the problem of combination of environmental and anthropogenic conditions for animal in cattle breeding the systematized approach allows to develop reasonable decision and solve the problem of interactivity between the animal organism and environment with the aim of receiving the highest stable level of productivity and high quality production, healthy animals under the combination of factors: natural (climatic) and anthropogenic (technological, technical, feeding, utilizing).